Capacidades estatais dos governos municipais nas políticas de ciência, tecnologia e inovação: as experiências de Campina Grande/PB, Recife/PE e Natal/RN - Melo, Cadmiel Mergulhão Onofre de (2022)
This research adresses state capacities – the resources, skills, knowledge and instruments in reach for use by the state (GRIN; DEMARCO; ABRUCIO, 2021; SOUZA, 2015) – as essential to the completion of the developmental process of any nation-state, specially through the promotion of technological innovation policies. Brazil is included in this challenge, where brazilian municipalities have been given federated entity responsibilities as a way of making public policies in tune with demands from the population, which have put them leading discussions about brazilian development (LOTTA; VAZ, 2015). However, the decentralisation of such responsibilities was not accompanied by the decentralisation of the decision power over those policies, nor the the concern of giving those municipalities the state capacities required to conduct their new roles (ARRETCHE, 2012; LOTTA; VAZ, 2015). Such scenario implicates reduced capacities that do not allow municipalities to propose science, technology and innovation (STI) policies, making them resort to the participation in institutional arrangements of such policies coordinated by other institutional actors, mainly those associated to the triple helix (ETZKOWITZ, 2013), such as policies for technological parks. In this way, the municipality participating in the arrangement is understood as a mean of taking advantage of the experience and its policy results in order to gain knowledge and resources on how to propose initiatives in STI, allowing for new state capacities to be built. This configuration is especially relevant to municipalities out of the brazilian industrial concentration zone, where a technological park can be a viable option as a starter for a STI research and economic sector, something that could “replace” the industry factor in promoting new technologies. In order to better understand this phenomenon, this research aims to investigate if state capacities engaged by the municipal governments of Natal/RN, Campina Grande/PB and Recife/PE in the institutional arrangements of the technological parks Metrópole Digital, Fundação Parque Tecnológico da Paraíba and Porto Digital originated the current state capacities of those governments in the policy area of science, technology and innovation. The methodology was conducted by a qualitative approach, making use of the multiple cases study (CHMILIAR, 2010; CRESWELL, 2003; KING; KEOHANE; VERBA, 1994), in which representatives from governments, universities, technological innovation economies and technological parks were interviewed and secondary data about the institutional arrangements and state capacities from the selected municipal governments were gathered. The results show that for two of the three cases there were evidences suggesting expanded state capacities since the arrangement, where the experience of the implementation in each case has established new or stronger partnerships between the municipal government and actors involved, including with the newly implemented technological parks, which matured overtime. That allowed the formation of a own municipal STI policy agenda that included initiaives ranging from the creation of own bureaucratic structures within the municipal government to the promotion of large-scale actions, together with local institutional actors, for the development of the area in their municipalities.